Demonstration of a 50 cm2 BiVO4 tandem photoelectrochemical-photovoltaic water splitting device. Issue 9 (10th July 2019) - Ahmet, Ibbi Y.; Ma, Yimeng; Jang, Ji-Wook; Henschel, Tobias; Stannowski, Bernd; Lopes, Tânia; Vilanova, António; Mendes, Adélio; Abdi, Fatwa F.; van de Krol, Roel
Abstract : Mitigation of ohmic losses and mass transport limitations enables a large area BiVO4 -based water splitting device with a solar-to-hydrogen efficiency of 2.1%. Abstract : In this paper, we demonstrate a new benchmark for a large area photoelectrochemical–photovoltaic (PEC–PV) solar water splitting device with a metal oxide-based top absorber. The stand-alone 50 cm 2 device consists of cobalt phosphate-coated tungsten-doped BiVO4 (CoPi /W:BiVO4 ) photoanodes combined with series-connected silicon heterojunction (SHJ) solar cells. We highlight the performance limitations for large area BiVO4 photoanodes and present initial attempts in overcoming these challenges. Specific challenges encountered are (i) the high resistivity of the FTO substrate, (ii) non-uniform CoPi deposition, and (iii) limited ionic conductivity of the 0.1 M phosphate buffer electrolyte typically used for small area BiVO4 devices. The former two problems were overcome by applying Ni lines to the FTO substrate, and the latter to some extent by increasing the electrolyte concentration to 2.0 M. Despite the high buffer concentration, the overall performance of the large area photoelectrodes was found to be limited by H + /OH − transport in this near-neutral pH electrolyte. This limitation results in H + /OH − depletion towards the center of the large area electrode and significant potential drop, which can be overcome by implementing a cell design with a small electrode-area-to-electrolyte-volume ratio. Our optimized photoanodes were then integrated into tandem PEC–PV devices in either a single or dual photoanode configuration. These 50 cm 2 PEC–PV devices demonstrate solar to hydrogen (STH) efficiencies of 1.9% (single CoPi /W:BiVO4 and 2-series connected SHJ cells) and 2.1% (dual CoPi /W:BiVO4 and 2-series connected SHJ cells). Optimized small area (0.24 cm 2 ) PEC–PV devices based on a similar configuration show a STH efficiency of up to 5.5%. Our results illustrate the challenges involved in the scale-up of solar water splitting devices and underline the importance of increased electrochemical engineering efforts in this developing field.